SURVEI TINGKAT KESEGARAN JASMANI SISWA KELAS V SDN PLOSO II/173 KEC. TAMBAK SARI SURABAYA - HAMZAH, FARIT (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract Ploso II/173 Public Elementary School is a school that is located in the district of Tambak Sari, Surabaya. Physical education learning process implemented in every morning, starting at 6:30 a.m. to 09:00 a.m. This school is a school that is quite dense in extracurricular activities with one extracurricular are futsal and swimming, followed by third, fourth, fifth grade. The problem that often occurs in the class, each completed lesson physical education students on average experienced fatigue, especially during a flag ceremony on Monday morning, students often fall unconscious especially fifth grade class. So in stints at schools, teachers are often faced with the fact, that the level of physical fitness of each student learners is very low, so that by the time in the flag ceremony many students who experience fatigue, especially during sports that require a lot of stamina high. This study aims to determine:  to reveal the physical fitness level student of boys and girls SDN Ploso II/173 Surabaya. Objectives of this study were fifth grade students of SDN Ploso II/173, amounting to 92 (ninety two) students. The method used in this analysis using quantitative descriptive method, while the process of data retrieval is done by using a test level of physical fitness Indonesia (TKJI). Among other s, running test in 40 m, hanging elbow bend test, baring sit test in 30 seconds, vertical jumping test, and a running test in 600 m, data analysis using the percentage The results obtained the following conclusions were: 1). Great level of physical fitness students at SDN Ploso II/173 son of the son of 49 students, a total of 3 students (6,12%) had a level of physical fitness to the excellent category, 22 students (44,89%) had a level of physical fitness with a good category, 14 students (28,57%) had a level of physical fitness to the medium category, and 10 students (20,41%) have this level of physical fitness with less category. 2).Great level of physical fitness of students at SDN Ploso II/173 from 43 female students, a total of 2 students (4,65%) had a good level of physical fitness at all, 13 students (30,23%) had good physical fitness by category, 20 students (46,51%) have this level of physical fitness to the medium category, and 8 students (18,6%) had levels of physical fitness with less category. Keywords:   Physical Fitness Level